2021
DOI: 10.15446/dyna.v88n219.94724
|View full text |Cite
|
Sign up to set email alerts
|

Landscape visual quality influence on noise pollution propagation in urban green areas

Abstract: The objective was to evaluate the influence of noise pollution on both visual and sound landscapes at the Botanical Garden and the São Lourenço Park in Curitiba, Brazil. Data were collected in three transects (A, B, and C), representing different vegetation densities. Landscape visual quality was characterized through a direct method for valuing landscape elements. The visual quality was classified as Good, Mean, or Bad. For the sound analysis, two INSTRUTHERM decibel meters, model DEC-470, with 1.5-decibel pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 18 publications
0
4
0
Order By: Relevance
“…Finally, the exposed model is more efficient compared to other convolutional network architectures that have been implemented in the recognition of common environmental sounds [3,17] with parameters between 25'636.712 and 143'667.240. Since it reported satisfactory results in accuracy and prediction speed for the dimensions of the model presented with 54,000 parameters.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, the exposed model is more efficient compared to other convolutional network architectures that have been implemented in the recognition of common environmental sounds [3,17] with parameters between 25'636.712 and 143'667.240. Since it reported satisfactory results in accuracy and prediction speed for the dimensions of the model presented with 54,000 parameters.…”
Section: Resultsmentioning
confidence: 99%
“…However, these applications initially developed for the military industry can be used in mining, surveillance of critical infrastructure, protection, and conservation of the environment [3,4]. Artificial intelligence provides solutions for the recognition of radio frequency [5] and audio signals at a very low cost, which have been developed with different objectives, such as the detection of drones [6] or the measurement of noise pollution [3]. The study of deep learning models in environmental settings is presented as a tool for monitoring infrastructures of environmental and material value.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies propose an alternative approach for calculating sound propagation in green areas. De Oliveira et al [75] found a highly significant relationship between the visual quality of the landscape and noise attenuation.…”
Section: Quiet Areas In Noisy Urban Environmentsmentioning
confidence: 98%
“…Additionally, incorporating vegetation has proven to be effective in reducing noise in urban settings. Landscaped areas planted with more vegetation and more complex vegetation structure are often effective in reducing significant levels of attenuated noise (Oliveira et al, 2021a;Oliveira et al, 2021b). Vegetation landscaping tends to absorb more sound as the distance between them and the traffic sound source decreases (Akay & Önder 2022).…”
Section: Introductionmentioning
confidence: 99%